How to evaluate progress in problem solving - Charles, Randall; Lester, Frank; Odaffer, Phares (Reston : Virginia : The national council of teachers of mathematics, 1987)
This book puts the goals of problem-solving evaluation in sharper foucs, describes several classroom evaluation techniques, and illustrates how these techniques might be used in practice."--Page 1.
Keywords: Problem solving -- Study and teaching; Mathematical ability -- Testing